A Single Bioinspired Hexameric Nickel Catechol–Alloxazine Catalyst Combines Metal and Radical Mechanisms for Alkene Hydrosilylation. Issue 35 (12th May 2022) - Das, Agnideep; Schleinitz, Jules; Karmazin, Lydia; Vincent, Bruno; Le Breton, Nolwenn; Rogez, Guillaume; Guenet, Aurélie; Choua, Sylvie; Grimaud, Laurence; Desage‐El Murr, Marine
Abstract: Mechanisms combining organic radicals and metallic intermediates hold strong potential in homogeneous catalysis. Such activation modes require careful optimization of two interconnected processes: one for the generation of radicals and one for their productive integration towards the final product. We report that a bioinspired polymetallic nickel complex can combine ligand‐ and metal‐centered reactivities to perform fast hydrosilylation of alkenes under mild conditions through an unusual dual radical‐ and metal‐based mechanism. This earth‐abundant polymetallic complex incorporating a catechol‐alloxazine motif as redox‐active ligand operates at low catalyst loading (0.25 mol%) and generates silyl radicals and a nickel‐hydride intermediate through a hydrogen atom transfer (HAT) step. Evidence of an isomerization sequence enabling terminal hydrosilylation of internal alkenes points towards the involvement of the nickel‐hydride species in chain walking. This single catalyst promotes a hybrid pathway by combining synergistically ligand and metal participation in both inner‐ and outer‐ sphere processes. Abstract : A dual metal and radical reactivity is enabled by a polymetallic nickel complex merging alloxazine and catechol redox‐active subunits. This is the first catalytic application of an alloxazine 3d metal complex and this complex promotes silyl radical generation and chain walking of internal alkenes.